Aggressive Aortic Arch and Carotid Replacement Strategy for Type A Aortic Dissection Improves Neurologic Outcomes - Trivedi, Dhaval; Navid, Forozan; Balzer, Jeffrey R; Joshi, Rama; Lacomis, Joan M; Jovin, Tudor G; Althouse, Andrew D; Gleason, Thomas G (The Annals of thoracic surgery, 2016)
International registries for acute type A aortic dissection (TAAD) demonstrate stagnant operative mortality rates in excess of 20% and stroke rates of 9% to 25%, with little global emphasis on stroke reduction or carotid involvement. Cerebral malperfusion with TAAD has been linked to poorer outcome. We hypothesize that concomitant carotid dissection or complex dissection flaps in the arch play a major role in stroke development and that aggressive reconstruction of the arch and carotid arteries can improve neurologic outcomes in TAAD. A standardized protocol focused on expedient care, neurocerebral protection, and common carotid and total arch reconstruction was developed for 264 consecutive TAADs. Arch and complete carotid replacement was based on arch dissection anatomy, carotid involvement, or an intraarch tear. Neurocerebral monitoring with continuous electroencephalogram/somatosensory evoked potentials was used in all cases. The postoperative stroke and hospital mortality rates were 3.4% and 9.1%, and stroke rates by extent of arch replacement were 4%, 3%, and 0% for hemiarch, total arch, and total arch with complete carotid replacement, respectively. An intraoperative change in the electroencephalogram/somatosensory evoked potentials was strongly predictive of stroke and had a negative predictive value of 98.2%. An algorithmic approach to TAAD including (1) rapid transport-to-incision-to-cardiopulmonary bypass established centrally, (2) neurocerebral monitoring, (3) liberal use of total arch replacement for clearly defined indications (and hemiarch for all others), and (4) common carotid arterial replacement for concomitant carotid dissections significantly improves outcomes.